2016
DOI: 10.1371/journal.pone.0148372
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Compound Icariin Activates Hypoxia Inducible Factor-1α in Chondrocytes and Promotes Articular Cartilage Repair

Abstract: Articular cartilage has poor capability for repair following trauma or degenerative pathology due to avascular property, low cell density and migratory ability. Discovery of novel therapeutic approaches for articular cartilage repair remains a significant clinical need. Hypoxia is a hallmark for cartilage development and pathology. Hypoxia inducible factor-1alpha (HIF-1α) has been identified as a key mediator for chondrocytes to response to fluctuations of oxygen availability during cartilage development or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 56 publications
3
69
0
Order By: Relevance
“…However, there is a significant reduction of iron deposition in mice orally administrated with icariin, indicating icariin could reduce iron accumulation in vivo. Many herba flavonoids (e.g., quercetin and galangin) were reported to have the ability to chelate iron ions (Park, Bae, & Lee, ), studies by Wang et al () demonstrated that icariin could chelate cellular iron ions, leading to the inhibition of PHDs‐catalyzed HIF prolyl hydroxylation and subsequently activate HIF‐1α/2α. Our results indicated that besides iron chelation effect, icariin also could regulate iron metabolism, and promote excreting excess iron.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a significant reduction of iron deposition in mice orally administrated with icariin, indicating icariin could reduce iron accumulation in vivo. Many herba flavonoids (e.g., quercetin and galangin) were reported to have the ability to chelate iron ions (Park, Bae, & Lee, ), studies by Wang et al () demonstrated that icariin could chelate cellular iron ions, leading to the inhibition of PHDs‐catalyzed HIF prolyl hydroxylation and subsequently activate HIF‐1α/2α. Our results indicated that besides iron chelation effect, icariin also could regulate iron metabolism, and promote excreting excess iron.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated effects of Sal B on passage 3/4 (P3/4) chondrocytes resembling those cultured cells for therapeutic applications. The P3/4 chondrocytes are successfully employed in clarification of regulatory role of factors on cellular functions in various cell models . However, accumulated evidence showed that passaged chondrocytes change their gene expression profiles, including matrix proteins, cytokines, matrix proteases and inhibitors, and signalling molecules , and dedifferentiate into a more fibroblastic state typically with decreased COL II and ACAN accompanied by increased COL I .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also demonstrated the involvement of hypoxia and HIF pathway for re-entry of cells in the cell cycle and for the cell contribution to organ regeneration (Ortmann et al, 2014;Brocato, Chervona, & Costa, 2014;Rios et al, 2016;Cho et al, 2015;Nakada et al, 2016;Zhang et al, 2015). Moreover, a relationship between HIF-1α induction in articular cartilage, cell proliferation, and cartilage repair has been reported (Wang et al, 2016). inhibiting DNA binding activity of HIF-1 or acriflavine, a direct inhibitor of HIF-1 because it prevents HIF-1 dimerization (Kong et al, 2005;Lee et al, 2009).…”
Section: Pl Induces the Expression Of Hif-1α That Takes Part In Thementioning
confidence: 98%
“…The cell cycle arrest of cardiomyocytes after birth was explained with the oxygen-rich postnatal environment (Puente et al, 2015). It was recently reported that induction of HIF-1α increased proliferation of cultured murine growth plate chondrocytes and promoted articular cartilage repair in an osteochondral defect mice model (Wang et al, 2016). The new finding that PL induces HIF-1α and that this factor is closely related to cell activation and proliferation opens a new perspective on the HIF-1α role during wound healing in different systems.…”
Section: In Cultured Cartilage Cells Pl Induced the Expression Of Himentioning
confidence: 99%